Pemanfaatan Bauran Media Leaflet dan Poster Meningkatkan Pengetahuan dan Sikap Personal Hygiene Penjamah Makanan - Suarianti, Ni Wayan; Sudiadnyana, I Wayan; Mahayana, I Made Bulda; Sujaya, I Nyoman (Poltekkes Kemenkes Denpasar, 2025)
ABSTRACT Background: Food handlers' behavior during food processing is closely related to the quality of the food produced and served to consumers. Improving personal hygiene knowledge and attitudes is a key factor in changing personal hygiene behavior among food handlers. The purpose of this study was to determine the effectiveness of education using a mix of leaflets and posters to improve personal hygiene knowledge and attitudes among food handlers.Method:.The study used a pre-experimental method with a One Group Pretest Posttest Design. Data were collected using a questionnaire targeting food handlers at 35 restaurants. Data were analyzed using a paired t-test.Result:.The average knowledge of personal hygiene before education increased from 6.20 to 9.48 after education, a 51.13 increase. The average personal hygiene attitude before education increased from 9.37 to 10.68 after education, a 12.66 increase. There was a significant difference in knowledge before and after education, with a significant difference of 0.000. Similarly, there was a significant difference in attitudes before and after education, with a significant difference of 0.003.Conclusion: Utilizing a media mix of leaflets and posters can improve food handlers' knowledge and attitudes about personal hygiene.